DAMPAK DISIPLIN KERJA SEBAGAI VARIABEL MODERATING PADA PENGARUH MOTIVASI KERJA, BUDAYA ORGANISASI, DAN LINGKUNGAN KERJA TERHADAP KINERJA NON ASN PADA DINAS PUPP KABUPATEN SITUBONDO - Kurniawan, Rafli Dwi; Fandiyanto, Randika; Minullah, Minullah (Jurnal Mahasiswa Entrepreneurship (JME), 2024)
Official service is a means that is a determinant in the development of a city. The direction of change in the development of a city can be seen through design and implementation by government agencies. HR is a factor that plays a significant role in almost all of these topics. The aim of this research is to analyze and test the influence of Work Motivation, Organizational Culture and Work Environment on Non-ASN Performance at the Situbondo Regency PUPP Service with moderation in the form of work discipline. The population in this research are non-ASN employees at the Situbondo Regency PUPP Service. The sample in this study was determined using the Slovin formula with random probability sampling technique. Data analysis and hypothesis testing in this research used the structural equation model - Partial Least Square (PLS-SEM). The results of the direct influence hypothesis test using Smart PLS 3.2.9, show that work motivation has a significant effect on performance, organizational culture has no significant effect on performance, the work environment has a significant effect on performance, and work discipline does not significantly moderate the effect of work motivation on performance. .